Medication persistence rates and predictive factors for discontinuation of antifibrotic agents in patients with idiopathic pulmonary fibrosis: a real-world observational study - Keiji Oishi; Tsunahiko Hirano; Yoriyuki Murata; Kazuki Hamada; Sho Uehara; Ryo Suetake; Yoshikazu Yamaji; Maki Asami-Noyama; Nobutaka Edakuni; Syuichiro Ohata; Toshiaki Utsunomiya; Kenji Sakamoto; et al. (Therapeutic Advances in Respiratory Disease, 2019)
Background: In patients with idiopathic pulmonary fibrosis (IPF), continuing treatment with antifibrotic agents is crucial to decrease the reduction of forced vital capacity and mortality rate. However, predictive factors for the discontinuation of antifibrotic agents are unknown. This study aims to investigate the clinical characteristics and predictive factors for the discontinuation of antifibrotic agents in patients with IPF. Methods: This was a double-center retrospective study that enrolled patients with IPF treated with pirfenidone or nintedanib between 2009 and 2017. We compared clinical parameters between the medication-continuing group and the discontinued group. The predictive factors were determined using Cox proportional hazards analyses. Results: A total of 66 subjects were included: 43 received pirfenidone and 23 received nintedanib. At 1 year, 23 of 66 patients had discontinued due to adverse events ( n  = 12), disease progression ( n  = 9), or death ( n  = 2). The characteristics of the discontinuation group were poor performance status (PS) and delay from diagnosis to treatment. In the receiver operating characteristic (ROC) analysis associated with the discontinuation of antifibrotic agents, PS was the highest area under the ROC curve (AUC) value (cut-off value, 2; AUC, 0.83; specificity, 63%; sensitivity, 87%). This finding was consistent even when analyzing, except for examples of death and adjusting for the type of antifibrotic agent. The treatment persistence rate by PS was PS 0–1 = 90%, PS 2 = 65%, and PS 3 = 19%. Analysis of the relationship between PS and administration period of antifibrotic agents revealed that delays from diagnosis to treatment led to worsening of dyspnea, a decline in lung function, and deterioration of PS. Conclusions: PS may be informative for predicting discontinuation of medication. Our data reinforced the importance of early initiation of antifibrotic treatment, and we suggest PS should be used as a guide for starting antifibrotic agents in everyday practice. The reviews of this paper are available via the supplementary material section.